United Republic of Tanzania : Selected Issues. (IMF Staff Country Reports; Country Report, 2016)
This Selected Issues paper examines productivity, growth, structural reforms, and macroeconomic policies in Tanzania. Tanzania experienced macroeconomic stabilization and significant structural change over the last three decades, including two major waves of reforms, first in the mid-1980s and more importantly in the mid-1990s. Both reform waves were followed by total factor productivity (TFP) and growth spurts. Over the recent period, TFP growth decreased, which coincided with a less strong reform drive. It is suggested that a TFP-led growth model is superior and that vigorous reforms are needed to foster further structural transformation of the economy and sustain high productivity gains and investment.